Regulation of ion homeostasis in plants: Current approaches and future challenges - Rouached, Hatem (Plant Signal Behav, 2010)
The dependency of plants on essential macro- and micro-elements to complete their life cycle serves as a major entry point of these elements into the global food web. However, plants often face depletion of one or more essential elements limiting their growth. Thus, in modern agriculture, improving plant mineral nutrition has gained fundamental importance in order to address the issue of sustainable food resources for the growing world population. Heavy fertilization of soil was, for long time, chosen as a strategy to cope with the deficiency of these elements. Yet, this strategy is neither economically nor ecologically conceivable at long-term. As an alternative, genetic and breeding approaches that provide plants new characteristics enabling them to grow in nutrient-depleted soils, has become a major focal interest. The research emphasis so far has been on elucidating the molecular physiology of individual nutritive elements. However, in practice, application of such knowledge is hindered by complex cross-talks, which are emerging in the face of new data, between these elements. Developing integrative approaches, combining genetic, comparative genomics and ‘omics’ platforms, is crucial to untangle the interconnected signaling networks regulating ion homeostasis in plants.